If g(x)


If $g(x)=x^{2}+x-2$ and $\frac{1}{2} g o f(x)=2 x^{2}-5 x+2$, then $f(x)$ is equal to

(a) $2 x-3$

(b) $2 x+3$

(c) $2 x^{2}+3 x+1$

(d) $2 x^{2}-3 x-1$


We will solve this problem by the trial-and-error method.
Let us check option (a) first.

If $f(x)=2 x-3$

$\frac{1}{2}(g o f)(x)=g(f(x))$

$=\frac{1}{2} g(2 x-3)$

$=\frac{1}{2}\left[(2 x-3)^{2}+(2 x-3)-2\right]$

$=\frac{1}{2}\left[4 x^{2}+9-12 x+2 x-3-2\right]$

$=\frac{1}{2}\left[4 x^{2}-10 x+4\right]$


$=2 x^{2}-5 x+2$

The given condition is satisfied by (a).
So, the answer is (a).

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now